Characterisations the bio-active compounds of bio-oil extracted from red meranti sawdust by fast pyrolysis - Nor Wahidatul Azura, Zainon Najib (2018)
Fast pyrolysis is a thermochemical conversion technology to convert biomass into bio-oil product. In this study, red meranti sawdust (RMS) was selected as biomass as feedstock to evaluate its potential to produce bio-oil by fast pyrolysis. The study covers the objective to investigate the parameters effect of process in optimising the bio-oil production and characterise the extracted bio-oil. Fast pyrolysis process was conducted in a bench-scale fluidized bed reactor, with the system consist of temperature controller, cyclone, condensers, nitrogen gas, flow meter, char and bio-oil collectors. In investigating the effect of pyrolysis condition, the experiments were run according to one-factor-at-a-time (OFAT) approach with the parameters involved were temperature, N2 flow rate, retention time and feed particles size. Results showed that bio-oil achieved maximum yield about 56.3 % at 450 °C of temperature, 25 L/min of N2 flow rate and 20 min of retention time for 0.3 mm of feed particles size. It can be concluded that the temperature was the most influential parameter for bio-oil yield. Physicochemical characterisation of bio-oil indicated bio-oil not suitable for transportation fuel due to high oxygen content. Through gas chromatography–mass spectrometry (GC-MS) analysis, phenolic was the dominant compound identified in bio-oil. Total sugars in bio-oil was 12.82 % area including levoglucosan yield was 8.97 % area. In determining the effect of washing treatment, RMS was washed with deionised (DI) water or diluted hydrochloric (HCl) acid. The efficiency of AAEM removal by DI water, 1.0M HCl and 2.0 M HCl were 66.39 %, 93.32 %, and 97.28 %, respectively. From FTIR analysis, washing treatment had strengthened the RMS chemical bonds. For bio-oil production, bio-oil extracted from RMS - DI water achieved maximum yield about 57.2 % at 450 °C of optimum temperature. In extracted bio-oil, washed RMS produced higher heavier compound and higher levoglucosan than raw RMS. In pyrolysis of impregnated RMS study, RMS was impregnated with CaCl2, CaSO4, FeCl2 or FeSO4. Among these feedstocks, RMS - FeSO4 enhanced the degradation process at lower temperatures with the maximum degradation of temperature has been shifted from 361 °C for RMS control to 314 °C for RMS - FeSO4. Through FTIR analysis, impregnated RMS with FeSO4 has weakened the RMS chemical bond. In extracted bio-oil, it consisted large range of molecular weight compounds and showed an increasing in levoglucosan yield. Levoglucosan was the highest in RMS - FeSO4 about 40.23 % area, with 42.24 % area of total anhydrosugars yield. In optimising bio-oil yield, central composite design (CCD) of response surface methodology (RSM) modelling was employed to develop mathematical model and optimise the process parameters. Through predicted model, results showed that the optimal pyrolysis process condition was obtained at 480 °C of temperature, 25 L/min of N2 flow rate and 24 min of retention time with 56.5 % of bio-oil yield and 2.11 % of error by experiment. Conclusion, RMS has a potential to produce bio-oil. With further treatment on bio-oil to remove oxygen content, this bio-oil can be applied to substitute conventional fuel. Impregnated treatment of RMS with FeSO4 reveals degradation process can be enhanced at lower temperature and increases levoglucosan in bio-oil. These findings are expected to provide some guidelines in future study to produce value-added product from other lignocellulose waste and further, the government concept of divert waste to wealth-product can be achieved.